THE ADVANTAGES AND CHALLENGES OF IMPLEMENTING SUKUK THROUGH BLOCKCHAIN TECHNOLOGY - Iman, Aldi Khusmufa Nur; Arifin, Sirajul (An-Nisbah: Jurnal Ekonomi Syariah, 2021)
Financial instruments must be able to adapt quickly in the 4.0 era. One of the Islamic financial innovations highlighted at this time is the application of blockchain technology-based sukuk. This study aims to determine specifically the advantages of applying sukuk through blockchain technology and to scale the point of view regarding the challenges faced in applying sukuk through blockchain technology. This research uses a qualitative approach. The data collection technique used is literature study by collecting data from previous studies in the form of documentation of articles, journals or books as well as publication data from other parties. The data analysis techniques used were data reduction, data presentation, and conclusion drawing. The results show that sukuk can get many benefits from blockchain technology. Although blockchain has its advantages, there are risks and challenges that need to be resolved. In responding to this challenge, it is necessary to have a harmonious synergy among all stakeholders, from Syari'ah scholars, academics, to regulators and industry